Pedoman pembalakan berdampak rendah untuk hutan dipterocarpa lahan rendah dan bukit di Indonesia - Dykstra, D.P.; Sist, P.; Fimbel, R. (Center for International Forestry Research, 1999)
These guidelines form the basis for defining the initial set of activities to be classified as Reduced-Impact Logging (RIL). They have been adapted to and will be tested in the local conditions that occur in the lowland and hill dipterocarp forest of the Bulungan Model Forest project in East Kalimantan, Indonesia. It is anticipated that through the implementation and supervision of the RIL practices described in this document, the timber concession operators (INHUTANI II) can expect to: reduce disturbances to soil and residual vegetation by at least 50% in comparison to conventional logging operations where these guidelines are not applied; limit overall direct impacts to the forest <25%; conserve wildlife and other forest resources, including non-timber forest products, threatened and endangered species, keystone plant resources, and water; diminish direct logging costs by at least 15%; and protect the long-term integrity and value of the permanent forest estate.